Síntese, caracterização, estudo fotofísico e interação molecular de novas calcogenoporfirinas derivadas da 5,10,15,20–tetrakis(pentafluorofenil)porfirina - Foletto, Patrícia (2019)
The present work had as main objective the synthesis of new chalcogenporphyrins derived from 5,10,15,20-Tetrakis(pentafluorophenyl)porphyrin, characterization, study of photophysical properties and analysis of biomolecular interactions of prepared chalcogenporphyrins derivatives. In connection with the objectives, a synthetic route was developed which allowed the synthesis of various compounds derived from 5,10,15,20-Tetrakis(pentafluorophenyl)porphyrin. Initially, were obtained (mono-, di-, or tri-substituted) selenium and (Mono, di, tri or tetrasubstituted) hydrogen-porphyrins derived from 5,10,15,20-tetrakis (pentafluorophenyl)porphyrin employing p-methyl-diphenyl diselenide as the source of arylcalcogen anion. Thus, the synthesis of selenium and hydrogenporphyrins involved the aromatic nucleophilic substitution reaction between 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin and a nucleophile derived from pmethyl diphenyl diselenide. The formation of the products depended only on rigid control of the reaction time and a series of 4 unpublished selenium and hydrogenporphyrins molecules was obtained in good yields (in the range of 57-99%). In addition, were preparared news symmetrical thioporphyrins derived from 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin employing different sources of arylsulfur anion. Synthesis of the symmetrical thioporphyrins also involved the aromatic nucleophilic substitution reaction between 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin and nucleophiles derived from diaryl disulfides. The products were formed in 15 minutes of reaction and obtained with yields ranging from 82-93%. Also, hydrogenporphyrin derived from 5,10,15,20- tetrakis(pentafluorophenyl)porphyrin was obtained employing p-methyl-diphenyl ditelluride. The product was formed in 10 minutes of reaction and obtained in 80% yield. In this methodology, the formation of the products in excellent yields, in short reaction time, without the use of base in the reactional medium, with the use of reagents of easy handling and odorless, unlike in the literature, for example, for the synthesis of thioporphyrins (TUXEN et al., 2011) (GOMES et al., 2011), was highlighted. In addition, the synthetic protocol proved to be comprehensive for several dichalcogenides, making it possible to obtain compounds with the most diverse complexity. The formation of the products was rationalized based on the nucleophilic capacity of the calcogen atom (Te> Se> S) and on the lability difference in the carbon-chalcogen bond (C-S> C-Se> CTe). The compounds were characterized by 1H and 19F nuclear magnetic resonance, high resolution mass spectrometry (HRMS-ESI(+)), electron spectroscopy in ultraviolet- visible region (UV-vis) and fluorescence emission spectroscopy. In addition, studies of fluorescence quantum yields and singlet oxygen generation were developed. Thus, all the porphyrins studied presented lower values than the standard (TPP) of singlet oxygen generation and quantum yields of fluorescence, and among them, the quantum yields of singlet oxygen generation found for most of the thioporphyrins compounds were lower when compared to the selenoaryl-porphyrins. In addition, the selenium and hydrogenporphyrins compounds were tested for photostability and presented satisfactory results, being an appreciable characteristic according to the principles of photodynamic therapy. The interactions of porphyrins with CT-DNA were evaluated both experimentally and through molecular docking, demonstrating that they interact preferentially in the minor groove of the DNA. Also, the interactions of selenium and hydrogenporphyrins with HSA were studied. In these tests variations in intensity in the emission range were observed which is an indication of interaction between the protein and the respective compounds.